Doc Watson : a life in music - Huffman, Eddie (Chapel Hill : The University of North Carolina Press, 2025)
"Arthel 'Doc' Watson (1923-2012) is arguably one of the most influential musicians Appalachia has ever produced. A musician's musician, Doc grew up on a subsistence farm in the North Carolina mountains during the Depression, soaking up traditional music and learning to play guitar even though he was blind. Rising to fame in the 1960s as part of the burgeoning folk revival scene, Doc became the face of traditional music for many listeners, racking up multiple Grammys and releasing dozens of albums over the course of his long career. Eddie Huffman tells the story of Doc's life and legacy, drawing on extensive interviews and hundreds of hours of archival research. In making the most comprehensive biography of Watson ever, Huffman gives us an affecting and informative portrait of the man they called Doc. Full of fascinating stories--from Doc's first banjo made from his grandmother's cat to the founding of MerleFest--this promises to be the definitive biography of the man and how he came to be synonymous with roots music in America and shows how his influence is still felt in music today"--
Introduction. Mountain man of steel -- My home's across the Blue Ridge Mountains -- Call him Doc -- It's now or never -- Your lone journey -- An unbroken circle -- Doc and the boys -- A short life of trouble -- Gonna lay down my old guitar -- New millennium -- Sweet heaven when I die -- Conclusion. After life.
Includes bibliographical references and index.
Online resource; title from PDF title page (JSTOR platform, viewed February 24, 2025).
JSTOR
Keywords: Watson, Doc; Bluegrass musicians -- United States -- Biography; Folk musicians -- United States -- Biography; Guitarists -- United States -- Biography; Musiciens de bluegrass -- États-Unis -- Biographies; Musiciens traditionnels -- États-Unis -- Biographies; Guitaristes -- États-Unis -- Biographies; MUSIC / Genres & Styles / Country & Bluegrass; BIOGRAPHY & AUTOBIOGRAPHY / Music; Electronic books; Biographies; Biographies